(untitled) (SigMe, 2025)
Acute pancreatitis (AP) is a frequent pathology that in severe cases carries a risk of infection of local collections. These collections are usually resolved with percutaneous drainage (not in this case). A 57-year-old male patient, hypertensive and diabetic, was referred to the hospital after a month of severe AP with infected peripancreatic necrosis. Percutaneous treatment was decided with active irrigation without resolution of complications. A step-up approach was implemented with progressive dilation of percutaneous accesses, performing retroperitoneoscopy and necrosectomy, with adjusted antibiotic therapy, achieving multimodal resolution.